Profile of patients affected by trauma in the oral and maxillofacial complex in a hospital in the north of Piauí - Alana Letícia de Sousa Medeiros; Layane de Aragão Torres; Almiro Mendes da Costa Neto; Luís Paulo da Silva Dias; Evaldo Sales Leal; Rogério Meneses Ibiapina Coelho (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: The objective of this work is to analyze and describe the profile of patients affected by trauma to the oral and maxillofacial complex treated in a hospital in the north of Piauí. Methods: The medical records of patients undergoing surgical treatment by the Oral and Maxillofacial Surgery and Traumatology Team of the Chagas Rodrigues Regional Hospital were evaluated, since the beginning of the program, between July 2022 and October 2023. Results: It was observed that male individuals in the 32-year-old age group are the most affected by facial trauma, corresponding to 80,68% of cases, with a predominance of injuries in the orbito-zygomatico-maxillary complex (OZMC), accounting for 39,56% of the total fractures in this study, with motorcycle accidents as the main etiological factor (76,14%), in these cases, the most common treatment procedure was osteosynthesis of the orbito-zygomatic-maxillary complex (32,97%). Conclusion: It is concluded that trauma should not only be seen as a medical complication, but also as a social and economic problem, therefore it is necessary to create and implement traffic awareness and prevention measures regarding facial trauma.